Bioactive glass composite hydrogel as well as preparation method and application thereof

The bioactive glass composite hydrogel is prepared by photocrosslinking of magnesium-doped bioactive glass and methacrylic acylated protein, which solves the problems of insufficient mechanical strength and bone regeneration in the prior art, achieves the effects of bone repair and immune regulation, and simplifies the preparation process, which is suitable for industrial applications.

CN120586150APending Publication Date: 2025-09-05遵义医科大学第二附属医院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510532428.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-25
Publication Date
2025-09-05

AI Technical Summary

Technical Problem

The existing bioactive glass composite hydrogels have problems such as insufficient mechanical strength, difficulty in promoting bone regeneration and immune regulation at the same time, complex preparation processes and difficult to industrialize.

Method used

Bioactive glass composite hydrogels were prepared by photocrosslinking of magnesium-doped bioactive glass and methacrylic acylated proteins. The magnesium-doped bioactive glass with a porous structure and large specific surface area was used to enhance the mechanical strength, and to regulate the immune microenvironment through magnesium ions to promote bone repair.

Benefits of technology

It significantly enhances the mechanical strength of the hydrogel, improves bone repair activity, has excellent osteogenic differentiation and immune regulation capabilities, and is simple and feasible in technology and is easy to industrialize.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120586150A_ABST
    Figure CN120586150A_ABST
Patent Text Reader

Abstract

The invention discloses bioactive glass composite hydrogel as well as a preparation method and application thereof. The bioactive glass composite hydrogel comprises a photo-crosslinking hydrogel matrix and magnesium-doped bioactive glass filled in the hydrogel, the photo-crosslinking hydrogel matrix is obtained by photo-curing and crosslinking methacrylic acid acylated protein; the magnesium-doped bioactive glass is a porous material. The magnesium-doped bioactive glass powder is doped into the hydrogel, so that the mechanical strength of the hydrogel can be remarkably enhanced, the bone repair activity of the hydrogel is remarkably improved compared with that of existing bioactive glass composite hydrogel, specifically, the expression of osteogenic differentiation related genes (BMP2, COL1, OPN and RUNX2) can be up-regulated, MPs can be induced to be polarized to M2 phenotype, the expression of M1 phenotype genes can be inhibited, and the bone repair activity of the hydrogel is remarkably improved. The polypeptide has excellent osteogenesis regulation and control performance and immune regulation capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of medical materials, and in particular relates to a bioactive glass composite hydrogel and a preparation method and application thereof. Background Art

[0002] In recent years, with the continuous development of bone defect treatment research such as bone tissue engineering, hope has been brought to bone defect repair. The ideal bone repair material should have the advantages of biocompatibility and biodegradability. At the same time, it should also have osteoconduction, high porosity, mechanical strength, a structure similar to the extracellular matrix, and the ability to effectively induce new bone formation. Continuous and dynamic osteogenesis and angiogenesis are key factors in the bone repair process. Among them, hydrogels are a type of high molecular polymer system that has excellent biocompatibility, loading capacity of various bioactive substances, and a hydrophilic network as an extracellular matrix mimic. They have been widely studied and applied in the biomedical field.

[0003] Bioactive glass has been put into clinical use in the last century due to its unique inorganic amorphous structure, bioactivity and bone binding properties. With the upgrading of the preparation process, the third-generation bioactive glass with a mesoporous structure and high specific surface area is more widely used in the field of bone tissue engineering. Its application methods are even more diverse, including drug loading or forming a composite scaffold with other biomaterials (such as polymers, hydrogels, etc.) for bone regeneration. However, the dense pores and low specific surface area of ​​ordinary mesoporous bioactive glass limit the mechanical properties and bioactivity of the overall scaffold. These shortcomings need to be covered up by increasing the proportion of glass, but this is not conducive to its degradation and absorption in the body. In addition, the bioactive glass composite hydrogels prepared by existing technologies generally have the following problems: 1) insufficient mechanical strength of the material; 2) it is difficult to achieve the effects of promoting bone regeneration and immune regulation at the same time; 3) the preparation process is complex and difficult to industrialize. Summary of the Invention

[0004] In order to overcome the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a bioactive glass composite hydrogel. The second object of the present invention is to provide a method for preparing the above-mentioned bioactive glass composite hydrogel. The third object of the present invention is to provide applications of the above-mentioned bioactive glass composite hydrogel. The fourth object of the present invention is to provide applications of the above-mentioned bioactive glass composite hydrogel. The preparation method of the present invention is simple and feasible. The prepared composite hydrogel scaffold not only has good mechanical strength and biocompatibility, induces stem cell proliferation and osteogenic differentiation, and induces M2 polarization of macrophages, but also can promote osteogenic differentiation of stem cells by mediating macrophage polarization, and can be used for the repair and regeneration of bone tissue defects.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A first aspect of the present invention provides a bioactive glass composite hydrogel, comprising a photocrosslinked hydrogel matrix and magnesium-doped bioactive glass filled in the hydrogel; the photocrosslinked hydrogel matrix is ​​obtained by photocuring and crosslinking methacrylated protein; the magnesium-doped bioactive glass is a porous material.

[0007] Preferably, the particle size of the magnesium-doped bioactive glass is in the range of 500-1200 nm.

[0008] More preferably, the particle size of the magnesium-doped bioactive glass is in the range of 500-1000 nm.

[0009] Preferably, the specific surface area of ​​the magnesium-doped bioactive glass is 300 to 750 m 2 / g.

[0010] More preferably, the specific surface area of ​​the magnesium-doped bioactive glass is 400 to 500 m 2 / g.

[0011] Preferably, the average pore size of the magnesium-doped bioactive glass is 5 to 15 nm.

[0012] More preferably, the average pore size of the magnesium-doped bioactive glass is 10 to 15 nm.

[0013] Preferably, the pore volume of the magnesium-doped bioactive glass is 1.2 to 1.6 cm 3 / g.

[0014] More preferably, the pore volume of the magnesium-doped bioactive glass is 1.4 to 1.6 cm 3 / g.

[0015] Preferably, the mass proportion of magnesium in the magnesium-doped bioactive glass is 1.5% to 5%.

[0016] More preferably, the mass proportion of magnesium in the magnesium-doped bioactive glass is 1.5% to 3%.

[0017] Preferably, the elemental composition of the magnesium-doped bioactive glass includes O, Mg, Si, Ca, and P.

[0018] More preferably, the composition of the magnesium-doped bioactive glass includes SiO2, P2O5, CaO, and MgO.

[0019] Trace metal ions such as magnesium ions play a wide range of regulatory roles in bone metabolism, such as balancing the functions of osteoblasts and osteoclasts, regulating the immune microenvironment, and promoting bone angiogenesis. Although inflammation is an early mechanism for initiating healing, biomaterials can effectively and timely eliminate inflammation and form an immune microenvironment that is conducive to bone regeneration, which is crucial for bone repair. However, there are currently few studies on the immune regulation of bone regeneration by bioactive glass hydrogels doped with metal ions, and bone immunity determines the efficiency of bone regeneration by coordinating the interaction between immune cells and bone tissue. In addition, the magnesium-doped bioactive glasses reported so far are rarely porous. The present invention dopes bioactive glass with magnesium ions, and further uses porous magnesium-doped bioactive glass with a large specific surface area and methacrylated protein to photocuring and cross-link to prepare a bioactive glass composite hydrogel. After the bioactive glass adopts a porous structure, the specific surface area is larger, the degradation rate is faster, and the rate of releasing trace magnesium ions is also accelerated, which is beneficial to bone repair. The prepared bioactive glass composite hydrogel can induce stem cell proliferation and osteogenic differentiation, induce M2 polarization of macrophages, and promote osteogenic differentiation of stem cells by mediating macrophage polarization, and can be used for the repair and regeneration of bone tissue defects.

[0020] Preferably, the method for preparing the magnesium-doped bioactive glass comprises the following steps:

[0021] Tethyl orthosilicate, a template, an alkaline catalyst and water are prepared into a mixed solution and reacted; then triethyl phosphate, calcium nitrate and magnesium nitrate are added to the reaction system in sequence, and after standing and aging, a precipitate is obtained by centrifugation; the precipitate is washed, dried and calcined to obtain the magnesium-doped bioactive glass.

[0022] More preferably, the template is cetyltrimethylammonium bromide or cetyltrimethylammonium chloride.

[0023] More preferably, the alkaline catalyst is sodium hydroxide or aqueous ammonia.

[0024] More preferably, the method comprises the following steps: adding the template agent into an aqueous solution containing ethanol, dissolving ethyl orthosilicate in cyclohexane, mixing the two and stirring them evenly, and adding a sodium hydroxide aqueous solution to carry out a catalytic reaction.

[0025] Further preferably, the mass volume ratio of the template agent to the ethanol-containing aqueous solution is (0.05-0.3) g:10 mL.

[0026] Further preferably, the volume ratio of ethanol to water in the ethanol-containing aqueous solution is 1:(1-3).

[0027] Further preferably, the mass volume ratio of the template agent to ethyl orthosilicate is (1-10) g:5 mL.

[0028] More preferably, the volume ratio of triethyl phosphate to ethyl orthosilicate is 1:(10-20).

[0029] More preferably, the time interval for adding the triethyl phosphate, calcium nitrate and magnesium nitrate is 0.5-4 hours.

[0030] More preferably, the static aging time is 12-48 hours.

[0031] More preferably, the usage ratio of the calcium nitrate tetrahydrate, magnesium nitrate and ethyl orthosilicate is (2-10) g: (1-5) g: 10 mL.

[0032] More preferably, the drying temperature is 40-80°C.

[0033] More preferably, the calcination temperature is 500-800°C.

[0034] More preferably, the calcination time is 2-8 hours.

[0035] More preferably, the calcination procedure specifically includes: heating from room temperature to 500-800° C. at a heating rate of 0.5-3° C. / min, and maintaining the temperature for 2-8 hours.

[0036] Preferably, the methacrylated protein includes at least one of methacrylated silk fibroin, methacrylated gelatin, methacrylated collagen, and methacrylated whey protein.

[0037] Methacrylated silk fibroin hydrogels not only possess a highly hydrated three-dimensional structure and extracellular matrix mimicry similar to traditional hydrogels, but can also be polymerized and molded under mild light conditions. This process is controllable, avoiding the toxicity issues associated with traditional chemical crosslinkers. The cured hydrogels exhibit controllable physicochemical properties, excellent biocompatibility, and degradation resistance, providing optimal conditions for cell and tissue growth.

[0038] The second aspect of the present invention provides a method for preparing the bioactive glass composite hydrogel according to the first aspect, comprising the following steps:

[0039] The magnesium-doped bioactive glass, methacrylated protein and a photoinitiator are mixed in a solvent to prepare a mixed sol, and the mixed sol is subjected to a photocuring reaction to prepare the acellular matrix bone hydrogel.

[0040] Preferably, the mass ratio of the magnesium-doped bioactive glass to the methacrylated protein is 1:(10-20).

[0041] Preferably, the solvent is a PBS buffer solvent.

[0042] Preferably, the photoinitiator is lithium phenyl-2,4,6-trimethylbenzoylphosphonate.

[0043] Preferably, the mixing method is stirring, the stirring time is 0.5-4 hours, and the stirring temperature is 15-40°C.

[0044] Preferably, the light curing time is 0.5-3 minutes.

[0045] Preferably, the photocuring is performed by irradiating with blue light.

[0046] The third aspect of the present invention provides the use of the bioactive glass composite hydrogel described in the first aspect in the preparation of a product that promotes bone tissue repair and regeneration.

[0047] Preferably, the product for promoting bone tissue repair and regeneration can induce macrophage polarization toward the M2 phenotype and inhibit the expression of M1 phenotype genes.

[0048] Preferably, the product for promoting bone tissue repair and regeneration can induce stem cell proliferation and osteogenic differentiation.

[0049] The fourth aspect of the present invention provides use of the bioactive glass composite hydrogel described in the first aspect in preparing an injection therapy for treating bone injuries.

[0050] The beneficial effects of the present invention are:

[0051] (1) The present invention provides a bioactive glass composite hydrogel. By incorporating magnesium-doped bioactive glass powder into the hydrogel, the mechanical strength of the hydrogel can be significantly enhanced. In addition, the bone repair activity of the hydrogel can be significantly improved compared to the existing bioactive glass composite hydrogel. Specifically, the expression of osteogenic differentiation-related genes (BMP2, COL1, OPN, RUNX2) can be upregulated. It can also induce MPs to polarize toward the M2 phenotype and inhibit the expression of M1 phenotype genes, thus having excellent osteogenesis regulation and immunomodulatory capabilities. The composite hydrogel of the present invention has excellent ability to fill irregular bone defects and good biocompatibility, which is conducive to the adhesion of the gel to the defective cartilage after molding.

[0052] (2) The preparation method of the present invention has a simple process and can be cured and formed under mild light conditions, avoiding the problem of toxicity associated with the introduction of traditional chemical cross-linking agents. The raw materials have been industrialized and are easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 The surface morphologies of the bioactive glass MBG and BG of Example 1; (A) is a SEM image; (B) is a TEM image;

[0054] Figure 2Surface area and pore structure analysis of the bioactive glass MBG and BG of Example 1; (A) is the N2 adsorption-desorption isotherm curve; (B) is the pore size distribution diagram;

[0055] Figure 3 The surface morphology of the hydrogels prepared in Example 1 and Comparative Examples 1-2;

[0056] Figure 4 The mechanical properties of the hydrogels prepared in Examples 1-3 and Comparative Examples 1-2; (A) is the compressive strength; (B) is the Young's modulus;

[0057] Figure 5 The water absorption rate (A), swelling rate (B), magnesium ion release performance (C), and degradation characteristics (D) of the hydrogels prepared in Example 1 and Comparative Examples 1-2; Note: *p<0.05, **p<0.01, ***p<0.001;

[0058] Figure 6 The results of BMSCs cell proliferation in the hydrogels prepared in Example 1 and Comparative Examples 1-2; Note: *p<0.05, **p<0.01, ***p<0.001;

[0059] Figure 7 ALP staining (A) and quantification (B) of hydrogel-induced osteogenic differentiation of BMSCs; Note: *p<0.05, **p<0.01, ***p<0.001;

[0060] Figure 8 The expression of BMSCs osteogenic differentiation-related genes (BMP2, COL1, OPN, RUNX2) induced by hydrogel on the 7th day (A) and the 14th day (B); Note: *p<0.05, **p<0.01, ***p<0.001;

[0061] Figure 9 Hydrogels promote the expression of RAW264.7 cell polarization genes; (A) Expression of MPs marker genes TNF-α, IL-1β, CD206, and ARG after co-culture of hydrogels and RAW264.7 cells for 1 day; (B) Expression of MPs marker genes TNF-α, IL-1β, CD206, and ARG after co-culture of hydrogels and RAW264.7 cells for 3 days; Note: *p<0.05, **p<0.01, ***p<0.001;

[0062] Figure 10 Figure 2 shows the staining (A) and quantification (B) of ALP expression in BMSCs under the action of MPs-conditioned medium on hydrogels; Note: *p<0.05, **p<0.01, ***p<0.001;

[0063] Figure 11 The expression of BMSCs osteogenesis-related genes (BMP2, COL1, OPN, RUNX2) on day 7 (A) and day 14 (B) in the presence of MPs-conditioned medium after hydrogel incubation; Note: *p<0.05, **p<0.01, ***p<0.001. DETAILED DESCRIPTION

[0064] The present invention is further described in detail below through specific examples. Unless otherwise specified, the raw materials used in the following examples can be obtained from conventional commercial sources or prepared and isolated by simple synthesis; unless otherwise specified, the processes used are conventional processes in the art.

[0065] Example 1

[0066] This embodiment provides a magnesium-doped bioactive glass composite hydrogel, the preparation method of which is as follows:

[0067] (1) Preparation of magnesium-doped bioactive glass: 3 g of hexadecyltrimethylammonium chloride was added to 300 mL of an aqueous solution containing ethanol (the volume ratio of ethanol to water was 1:2), 5 mL of ethyl orthosilicate was dissolved in 30 mL of cyclohexane, and the two were mixed and stirred at 1000 rpm for 2 hours; 0.3 mL of The catalytic reaction was carried out in a 500 mM sodium hydroxide aqueous solution for 0.5 h; 0.35 mL of triethyl phosphate was added and the reaction was carried out for 1 hour; 3 g of calcium nitrate tetrahydrate was then added and the reaction was carried out for 0.5 hour; 1.5 g of magnesium nitrate was then added to the solution, and the solution was allowed to stand for 24 hours. The solution was then centrifuged at 6000 rpm for 1 hour to obtain a white precipitate, which was washed alternately with anhydrous ethanol and deionized water for 20 minutes each time for 3 times, dried at 50 degrees Celsius for 12 hours, and calcined at 650 degrees Celsius for 4 hours (heating rate of 2 degrees Celsius / minute) to obtain magnesium-doped bioactive glass powder (particle size range 500-600 nm; the mass ratio of magnesium in the bioactive glass was 1.72%, and the specific surface area was 444 m 2 / g, the average pore diameter is 13nm, and the pore volume is 1.48cm 3 / g).

[0068] (2) Preparation of magnesium-doped bioactive glass composite hydrogel: 60 mg of lithium phenyl-2,4,6-trimethylbenzoylphosphonate was added to 20 mL of PBS solution. 3 g of methacrylated silk fibroin was dissolved in the above solution and dissolved at room temperature to form a methacrylated silk fibroin solution. 0.3 g of magnesium-doped bioactive glass was then added to the solution and stirred at 25 degrees Celsius for 1 hour to uniformly disperse it. The solution was transferred into a mold and irradiated with blue light for 1 minute to obtain a magnesium-doped bioactive glass / silk fibroin hydrogel.

[0069] Example 2

[0070] This embodiment provides a magnesium-doped bioactive glass composite hydrogel, the preparation method of which is as follows:

[0071] (1) Preparation of magnesium-doped bioactive glass: 1.5 g of hexadecyltrimethylammonium chloride was added to 300 mL of an aqueous solution containing ethanol (the volume ratio of ethanol to water was 1:3), 5 mL of ethyl orthosilicate was dissolved in 15 mL of cyclohexane, and the two were mixed and stirred at 400 rpm for 4 hours; 1 mL of The catalytic reaction was carried out in a 100 mM sodium hydroxide aqueous solution for 1 hour; 0.25 mL of triethyl phosphate was added and the reaction was carried out for 4 hours; then 1 g of calcium nitrate tetrahydrate was added and the reaction was carried out for 4 hours; then 0.5 g of magnesium nitrate was added to the solution, and the mixture was allowed to stand for 12 hours. The mixture was centrifuged at 2000 rpm for 1 hour to obtain a white precipitate, which was washed alternately with anhydrous ethanol and deionized water once, each for 45 minutes, dried at 40 degrees Celsius for 24 hours, and calcined at 500 degrees Celsius for 8 hours (heating rate of 3 degrees Celsius / minute) to obtain magnesium-doped bioactive glass powder (particle size range 800-1200 nm; the mass proportion of magnesium in the bioactive glass was 1.5%, and the specific surface area was 750 m 2 / g, average pore diameter of 5nm, pore volume of 1.2cm 3 / g);.

[0072] (2) Preparation of magnesium-doped bioactive glass composite hydrogel: 90 mg of lithium phenyl-2,4,6-trimethylbenzoylphosphonate was added to 20 mL of PBS solution. 8 g of methacrylated silk fibroin was dissolved in the above solution and dissolved at room temperature to form a methacrylated silk fibroin solution. 0.4 g of magnesium-doped bioactive glass was then added to the solution and stirred at 35 degrees Celsius for 1 hour to uniformly disperse it. The solution was transferred into a mold and irradiated with blue light for 0.5 minutes to obtain a magnesium-doped bioactive glass / silk fibroin hydrogel.

[0073] Example 3

[0074] This embodiment provides a magnesium-doped bioactive glass composite hydrogel, the preparation method of which is as follows:

[0075] (1) Preparation of magnesium-doped bioactive glass: 9 g of hexadecyltrimethylammonium bromide was added to 300 mL of an aqueous solution containing ethanol (the volume ratio of ethanol to water was 1:1), 5 mL of ethyl orthosilicate was dissolved in 50 mL of cyclohexane, and the two were mixed and stirred at 2000 rpm for 0.5 h; 0.1 mL of A 1000 mM sodium hydroxide aqueous solution was used for catalytic reaction for 1 hour; 0.5 mL of triethyl phosphate was added and the reaction was carried out for 2 hours; then 5 g of calcium nitrate tetrahydrate was added and the reaction was carried out for 0.5 hour; then 2.5 g of magnesium nitrate was added to the solution, and after standing and aging for 48 hours, the solution was centrifuged at 12000 rpm for 0.5 hour to obtain a white precipitate, which was washed alternately with anhydrous ethanol and deionized water twice, each for 10 minutes, dried at 80 degrees Celsius for 6 hours, and calcined at 800 degrees Celsius for 2 hours (heating rate of 0.5 degrees Celsius / minute) to obtain magnesium-doped bioactive glass powder (particle size range of 600-900 nanometers; the mass proportion of magnesium in the bioactive glass was 5%, and the specific surface area was 300 m 2 / g, average pore diameter of 15nm, pore volume of 1.6cm 3 / g).

[0076] (2) Preparation of magnesium-doped bioactive glass composite hydrogel: 30 mg of lithium phenyl-2,4,6-trimethylbenzoylphosphonate was added to 20 mL of PBS solution. 1 g of methacrylated silk fibroin was dissolved in the above solution and dissolved at room temperature to form a methacrylated silk fibroin solution. 0.1 g of magnesium-doped bioactive glass was then added to the solution and stirred at 10°C for 1 hour to uniformly disperse it. The solution was transferred into a mold and irradiated with blue light for 2 minutes to obtain a magnesium-doped bioactive glass / silk fibroin hydrogel.

[0077] Comparative Example 1

[0078] This comparative example provides a bioactive glass composite hydrogel, the preparation method of which is substantially the same as that of Example 1, except that the bioactive glass is not doped with magnesium. The specific preparation method is as follows:

[0079] (1) Preparation of bioactive glass: 3 g of hexadecyltrimethylammonium chloride was added to 300 mL of an ethanol-containing aqueous solution (the volume ratio of ethanol to water was 1:2), 5 mL of ethyl orthosilicate was dissolved in 30 mL of cyclohexane, and the two were mixed and stirred at 1000 rpm for 2 hours; 500 mM of sodium hydroxide aqueous solution was added for catalytic reaction and 0.35 mL of triethyl phosphate was added and reacted for 1 hour. Subsequently, 3 g of calcium nitrate tetrahydrate was added and reacted for 0.5 hours. After standing and aging for 24 hours, a white precipitate was obtained by centrifugation at 6000 rpm for 1 hour. The precipitate was washed alternately with anhydrous ethanol and deionized water for 3 times, each time for 20 minutes, dried at 50 degrees Celsius for 12 hours, and calcined at 650 degrees Celsius for 4 hours (heating rate of 2 degrees Celsius / min) to obtain bioactive glass powder (particle size range of 500-600 nm; specific surface area of ​​453 m 2 / g, the average pore diameter is 11nm, and the pore volume is 1.35cm 3 / g).

[0080] (2) Preparation of bioactive glass composite hydrogel: 60 mg of lithium phenyl-2,4,6-trimethylbenzoylphosphonate was added to 20 mL of PBS solution. 3 g of methacrylated silk fibroin was dissolved in the above solution and dissolved at room temperature to form a methacrylated silk fibroin solution. 0.3 g of bioactive glass was then added to the solution and stirred at 25 degrees Celsius for 1 hour to uniformly disperse it. The solution was transferred into a mold and irradiated with blue light for 1 minute to obtain a bioactive glass / silk fibroin hydrogel.

[0081] Comparative Example 2

[0082] This comparative example provides a silk fibroin hydrogel, the preparation method of which is as follows:

[0083] Add 60 mg of lithium phenyl-2,4,6-trimethylbenzoylphosphonate to 20 mL of PBS. Dissolve 3 g of methacrylated silk fibroin in the solution at room temperature to form a methacrylated silk fibroin solution. Pour the solution into a mold and irradiate with blue light for 1 minute to obtain a silk fibroin hydrogel.

[0084] Experimental characterization

[0085] The bioactive glass and hydrogel prepared in Examples 1-3 (partially only Example 1 is shown) and Comparative Examples 1-2 (partially only Comparative Example 2 is shown) were subjected to the following performance evaluations. The results are shown in FIG. Figures 1 to 11 .

[0086] 1. Surface morphology characterization of bioactive glass

[0087] The microscopic mesoporous morphology and structure of the bioactive glass were characterized using a high-resolution field-emission scanning electron microscope (Merlin) from Carl Zeiss, Germany, and a transmission electron microscope (JEM-2100HR) from JEOL Ltd. The element types and element distribution on the scaffold surface were characterized and observed using an energy dispersive spectrometer (EDS) operating at an accelerating voltage of 15 kV.

[0088] The surface morphology of the magnesium-doped bioactive glass (MBG) of Example 1 and the bioactive glass (BG) of Comparative Example 1 is shown in FIG. Figure 1 As shown in (A) and (B) in Figure 1 It can be seen that the prepared BG and MBG have good dispersibility, a loose and porous surface, and the pores of the glass microspheres are radially distributed. In addition, the surface morphology characterization results of MBG in Examples 2-3 are similar. EDS element analysis is shown in Table 1:

[0089] Table 1 Elemental chemical composition of bioactive glass

[0090]

[0091] Table 1 shows that the MBG of Example 1 contains 1.72% of magnesium, and the remaining elements such as oxygen, silicon, calcium and phosphorus are similar to those of BG. In addition, the MBG of Examples 2 and 3 contain 1.5% and 5% respectively.

[0092] 2. Pore structure analysis of bioactive glass

[0093] The mesoporous structure was characterized by using a surface area and pore size analyzer (NOVA4200e) from Quantachrome Instruments. The test conditions were 250°C for 4 hours. The N2 adsorption-desorption curves of the magnesium-doped bioactive glass (MBG) of Examples 1-3 and the bioactive glass (BG) of Comparative Example 1 were analyzed to calculate their specific surface area, pore volume, average pore size and distribution. The results are shown in Figure 2. Figure 2 shown.

[0094] Figure 2 As can be seen from (A) in Figure 1, the N2 adsorption-desorption curves of BG and MBG of Example 1 conform to the type IV isotherm of mesoporous materials. The pore size distribution calculated using the BJH pore size distribution model is shown in the curves below. Figure 2 As shown in (B), the mesopore size distribution of glass microspheres is between 3-50nm. After calculation, it can be concluded that the specific surface area of ​​BG is 453m 2 / g, pore volume 1.35cm 3 / g, the average pore diameter is 11nm, and the specific surface area of ​​MBG in Example 1 is 444m 2 / g, pore volume 1.48cm 3 / g, and the average pore diameter is 13nm. The pore diameter data of MBG of Examples 2-3 were further calculated.

[0095] 3. Surface morphology of hydrogel

[0096] The surface morphology of Example 1 and Comparative Examples 1-2 was observed by scanning electron microscopy. Figure 3 As shown, the methacrylylated silk fibroin hydrogel (Comparative Example 2) has a macroporous structure and good pore connectivity, while the pore walls inside the hydrogel encapsulating the bioactive glass microspheres (Example 1, Comparative Example 1) become thinner and the pore structure becomes more irregular.

[0097] 4. Mechanical strength of hydrogel

[0098] Stent compression tests were conducted using a universal testing machine (INSTRON 5967) at room temperature at a speed of 1 mm / min. Five samples were prepared for each group. The samples had a diameter of 10 mm and a height of 8 mm. The compressive strength of the hydrogel was determined as the stress at which the compression deformation reached 90% on the stress-strain curve.

[0099] The mechanical strength results of the hydrogel are as follows Figure 4 As shown, the compressive strength and Young's modulus of the other groups were improved compared to the hydrogel in Comparative Example 2. Combined with the conclusion of Experimental Characterization 3 above, it is shown that the pore structure of the hydrogel platform is significantly affected by BG or MBG, and bioactive glass can enhance the compressive performance of the scaffold.

[0100] 5. Swelling, degradation and magnesium ion release properties of hydrogels

[0101] In order to evaluate the swelling capacity of the hydrogels of Example 1 and Comparative Examples 1-2, the hydrogel of Example 1 was denoted as MBS, and the hydrogels of Comparative Examples 1 and 2 were denoted as BS and S, respectively, the same below. The freeze-dried hydrogels were first weighed and the initial mass was recorded as W. a The hydrogel was then swollen in PBS solution at 37°C for 24 hours, and the liquid on the surface of the hydrogel scaffold was carefully removed with filter paper, and the weight was recorded as W. b The swelling ratio of the hydrogel was calculated using the following formula (1):

[0102] Swelling rate (%) = (W b -W a ) / W b ×100%(1);

[0103] In order to evaluate the degradation of the hydrogel, the PBS degradation method was used. The freeze-dried hydrogel was weighed and the initial mass was recorded as W dThe hydrogel was then immersed in PBS solution and placed in a shaker at 37°C and 100 rpm. The hydrogel was taken out at specific time points (1, 3, 7, and 14 days), washed with deionized water and anhydrous ethanol, freeze-dried, and weighed. The mass was recorded as W f The residual mass of the hydrogel was calculated using the following formula (2):

[0104] Mass residual rate (%) = W f / W d ×100%(2);

[0105] Accurately weigh 5 mg of MBG powder from Example 1 and prepare a 0.5 cm 3 MBS of 100 μg / mL were immersed in 3 mL of PBS. The PBS was removed on days 1, 3, 7, and 14, and the magnesium ion content in the liquid was analyzed using ICP-OES (Thermo Fisher Scientific, USA).

[0106] The swelling, degradation and magnesium ion release performance of the hydrogel are shown in Figure 2. Figure 5 As shown in Figure 2, the addition of BG or MBG changed the molecular chain structure of methacrylylated silk fibroin, resulting in a decrease in the swelling rate and water absorption rate of the hydrogel ( Figure 5 (A) and (B)). In the degradation experiment, the degradation rates of BS and MBS were significantly reduced, which is beneficial for providing medium around bone defects for a long time to promote repair ( Figure 5 (D) in the.

[0107] In particular, in the 28-day magnesium ion release experiment, MBG and MBS can continuously release magnesium ions. Due to the encapsulation of the hydrogel, the magnesium ion release performance of Example 1 is lower than that of MBG ( Figure 5 (C) in the.

[0108] 6. Hydrogel’s ability to promote cell proliferation

[0109] Rat bone marrow mesenchymal stem cells (BMSCs) were revived and cultured in a constant-temperature cell culture incubator at 37°C with a carbon dioxide concentration and 5% humidity. BMSCs were cultured in Dulbecco's Modified Eagle's Medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 100 μg / mL penicillin, and 100 μg / mL streptomycin. Cells were passaged when they reached 70%-80% confluency. The cells used in this experiment were passages 3-5. All hydrogels were sterilized by cobalt-60 irradiation before the experiment.

[0110] BMSCs were selected as the evaluation cells. Briefly, sterilized hydrogel samples were placed in a 48-well plate, and 1×10 4After 1, 3, and 7 days of culture, the culture medium was removed, and the cell proliferation activity on different hydrogels was assessed using a CCK-8 assay, and the OD value was measured using a microplate reader.

[0111] BMSCs cells were selected as evaluation cells and co-cultured with hydrogels, and a blank control group was set up. Figure 6 The BMSCs cell proliferation results of the hydrogels prepared in Example 1 and Comparative Examples 1-2 were compared with the other groups. The MBS in Example 1 could significantly promote the proliferation of BMSCs, followed by the Comparative Example 1 group, while there was no significant difference between the Comparative Example 2 group and the blank group.

[0112] 7. Evaluation of the in vitro osteogenic properties of hydrogels

[0113] 1×10 5 BMSCs were added to a 48-well plate containing the hydrogel sample and a blank well. After 24 hours of culture, the supernatant was aspirated and osteogenic induction medium (100 mL complete culture medium + 0.39 mg dexamethasone + 1.76 mg vitamin C + 306.11 mg sodium β-glycerophosphate) was added to each well. The medium was changed regularly. After 7 and 14 days of osteogenesis induction, the expression of osteogenic marker genes Runt-related transcription factor 2 (RUNX2), osteogenin (OPN), type I collagen (COLⅠ), and bone morphogenetic protein-2 (BMP-2) in the cells was detected by real-time fluorescence quantitative PCR, using GAPDH as a reference gene. After 7 days of osteogenesis induction, the scaffolds were stained for ALP using an ALP staining kit. After 14 days of osteogenesis induction, the scaffolds were stained with Alizarin Red staining solution, and the calcium nodule deposition on the scaffolds was observed under a microscope.

[0114] Figure 7 The prepared hydrogel had good biocompatibility. BMSCs were co-cultured with the hydrogel and induced to osteogenic growth for 7 days. ALP staining and quantitative analysis were performed. The alkaline phosphatase (ALP) level in the Example 1 group was the highest, followed by the Comparative Example 1, Comparative Example 2, and the blank group.

[0115] The results of the expression of genes related to osteogenic differentiation of BMSCs (BMP2, COL1, OPN, RUNX2) promoted by hydrogel are as follows Figure 8As shown. In the early stage of osteogenic differentiation, the expression levels of osteogenic genes (BMP2, COL1, OPN, RUNX2) in the hydrogel groups of Example 1 and Comparative Example 1 were significantly higher than those in Comparative Example 2 and the blank group. Among them, the expression of osteogenic genes in Example 1 group was the most significant, followed by Comparative Example 1 group. After 14 days of osteogenic induction, compared with the other groups, Example 1 group still upregulated the expression of BMP2, COL1, OPN, and RUNX2 the most significantly. The Comparative Example 2 group and the blank group were weaker than the Comparative Example 1 group, and there was no significant difference in the expression of BMP2 and RUNX2. In summary, the addition of glass microspheres to the hydrogel can enhance its in vitro osteogenic performance, among which the MBS group has the best performance in promoting BMSCs osteogenic differentiation.

[0116] 8. Evaluation of the immunomodulatory properties of hydrogels in vitro

[0117] Macrophage RAW264.7 cells were plated at 5 × 10 4 Cells were seeded onto the hydrogel samples in 48-well plates at a density of 100 cells / mL. On days 1 and 3, the culture medium was removed, and the expression of macrophage M1 marker genes (TNF-α and IL-1β) and M2 marker genes (CD206 and ARG) was measured using real-time quantitative PCR. GAPDH was used as a reference gene. Note: The culture medium from each hydrogel group on day 3 was collected and mixed with osteogenic induction solution at a ratio of 1:5 to prepare MP-conditioned medium for later use.

[0118] The polarization state of MPs (microphysiological system) affects the process of bone regeneration. Figure 9 It was found that in the process of each group of hydrogels inducing polarization of RAW264.7 cells, the hydrogel group was significantly better than the blank group. Compared with the comparative example 2 group, BG and MBG gave the hydrogel a stronger ability to regulate the polarization of MPs to the M2 phenotype. Among them, compared with the comparative example 1 group, the performance of the embodiment 1 group in upregulating the expression of MPs M2 marker genes (CD206, ARG) and inhibiting the expression of M1 marker genes (TNF-α, IL-1β) was more significant. In order to evaluate the potential of hydrogel-mediated MPs M2 phenotypic polarization to promote BMSCs osteogenic differentiation, BMSCs were cultured using MPs conditioned medium. In ALP staining and quantification, the hydrogel was significantly better than the blank group, among which the embodiment 1 group was the most significant ( Figure 10 ). At each time point, compared with other groups, the expression of osteogenic genes (BMP2, COL1, OPN, RUNX2) in Example 1 group was the most significant, followed by the comparative example 1 group, and the weakest was the blank group ( Figure 11 ). According to the above cell experiment results, compared with other groups, the hydrogel of Example 1 has stronger immunomodulatory ability, induces MPs to polarize toward the M2 phenotype, inhibits the expression of M1 phenotype genes, and has the strongest osteogenic regulation performance.

[0119] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A bioactive glass composite hydrogel, characterized in that: The invention comprises a photo-crosslinked hydrogel matrix and magnesium-doped bioactive glass filled in the hydrogel; the photo-crosslinked hydrogel matrix is ​​obtained by photocuring and crosslinking methacrylic acid acylated protein; and the magnesium-doped bioactive glass is a porous material.

2. The bioactive glass composite hydrogel according to claim 1, characterized in that The magnesium-doped bioactive glass meets at least one of the following requirements: a) the particle size of the magnesium-doped bioactive glass is in the range of 500-1200 nm; b) The specific surface area of ​​the magnesium-doped bioactive glass is 300 to 750 m 2 / g; c) the average pore size of the magnesium-doped bioactive glass is 5 to 15 nm; d) The pore volume of the magnesium-doped bioactive glass is 1.2 to 1.6 cm 3 / g; e) the mass proportion of magnesium in the magnesium-doped bioactive glass is 1.5% to 5%; f) The element composition of the magnesium-doped bioactive glass includes O, Mg, Si, Ca, and P.

3. The bioactive glass composite hydrogel according to claim 1, characterized in that The preparation method of the magnesium-doped bioactive glass comprises the following steps: Tethyl orthosilicate, a template, an alkaline catalyst and water are prepared into a mixed solution and reacted; then triethyl phosphate, calcium nitrate and magnesium nitrate are added to the reaction system in sequence, and after standing and aging, a precipitate is obtained by centrifugation; the precipitate is washed, dried and calcined to obtain the magnesium-doped bioactive glass.

4. The bioactive glass composite hydrogel according to claim 3, characterized in that The time interval for adding the triethyl phosphate, calcium nitrate and magnesium nitrate is 0.5-4h; And / or, the static aging time is 12-48 hours.

5. The bioactive glass composite hydrogel according to claim 4, characterized in that The usage ratio of the calcium nitrate tetrahydrate, magnesium nitrate and ethyl orthosilicate is (2-10) g: (1-5) g: 10 mL.

6. The bioactive glass composite hydrogel according to claim 1, characterized in that The methacrylated protein includes at least one of methacrylated silk fibroin, methacrylated gelatin, methacrylated collagen, and methacrylated whey protein.

7. The method for preparing the bioactive glass composite hydrogel according to any one of claims 1 to 6, characterized in that: The steps include: The magnesium-doped bioactive glass, methacrylated protein and a photoinitiator are mixed in a solvent to prepare a mixed sol, and the mixed sol is subjected to a photocuring reaction to prepare the acellular matrix bone hydrogel.

8. The method for preparing the bioactive glass composite hydrogel according to claim 7, characterized in that: The mass ratio of the magnesium-doped bioactive glass to the methacrylated protein is 1:(10-20).

9. Use of the bioactive glass composite hydrogel according to any one of claims 1 to 6 in the preparation of products for promoting bone tissue repair and regeneration.

10. Use of the bioactive glass composite hydrogel according to any one of claims 1 to 6 in the preparation of an injection therapy for treating bone injuries.